Semiclassical Diffractive Scattering for Transport Through Open Rectangular Microstructure (Journal of Atomic and Molecular Sciences, 2015)
We study the transport through weakly open rectangular billiards by a newsemiclassical approach within the framework of the Fraunhofer diffraction. Based ona Dyson equation for the semiclassical Green's function, the transmission amplitudecan be expressed as the sum over all classical trajectories connecting the entrance andthe exit leads. We find that the peak positions of the transmission power spectrum notonly correspond to classical trajectories but associate with a lot of nonclassical trajectoriesand the contributions to the power spectrum of the transmission amplitude forthe first mode are largely depending on the classical trajectories with small incidentangles showing a good agreement with the diffracted angular distribution within theframework of the diffractive scattering effect at the lead openings.
Keywords: Semiclassical approach; Fraunhofer diffraction; transmission amplitude.